Acetic Acid Suppresses Perennial Ryegrass Growth In Vitro by Disrupting Gibberellin and Auxin Homeostasis and Restricting Cell Expansion - Hao Guan; Caiyi Xie; Weiyu Jia; Ruiting Ouyang; Yuhan Xia; Yuhan Fu; Yi Man; Huaiyang Hou; Yingjun Chi; Bin Xu; Jing Zhang (Journal of Plant Growth Regulation, 2026)

Transcriptome Analysis Revealed Potential Immune-Related Genes of Head Kidney in the Yellow Catfish (Pelteobagrus fulvidraco) Challenged with Aeromonas hydrophila - Senhao Jiang; Yuting Lei; Ti Wang; Ruiting Ma; Chunqiang Hou; Qiuning Liu (Fishes, 2024)
Yellow catfish (Pelteobagrus fulvidraco) is an important freshwater fish species in aquaculture. However, as intensive farming has rapidly expanded, infectious diseases caused by various bacteria, such as Aeromonas hydrophila, have also increased. We conducted a transcriptomic analysis of head kidney from P. fulvidraco stimulated by A. hydrophila strain SHOU. A total of 43,249 unigenes with an average length of 1342 bp were obtained following assembly and annotation. By analyzing GO and KEGG enrichment, many differentially expressed genes (DEGs) and pathways related to immunity were identified. Out of the 973 DEGs that were identified, 553 were upregulated and 420 were downregulated. Moreover, KEGG enrichment analysis revealed that the innate immune system, including the TNF signaling pathway, NF-kappa B signaling pathway, and the Toll-like receptor signaling pathway involved in the defense, is activated against infectious response. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis demonstrated that immune response genes were upregulated in response to A. hydrophila stimulation compared to the control. In conclusion, this study provides valuable insights into the immune defense mechanism of P. fulvidraco and sheds light on the host immune genes involved in the response to bacterial infection.

Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution - Haiyan Ding; Ruiting Hou; Yun Li; Beibei Zhang; Baobao Zhao; Kun Liu (Food Additives & Contaminants: Part A, 2020)